2017
DOI: 10.1007/s13365-017-0519-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of varicella zoster virus infections of the central nervous system in the elderly: a large tertiary hospital-based series (2007–2014)

Abstract: The aim of the study was to describe the clinical and epidemiological characteristics of the central nervous system (CNS) infection by varicella zoster virus (VZV) in patients older than 65 years in a tertiary community hospital. We retrospectively analysed the results of cerebrospinal fluid (CSF) testing in patients older than 65 years between 2007 and 2014 with clinically suspected VZV infection with CNS involvement. Patients whose CSF samples were positive for VZV DNA were included, as were those with negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Absence of the typical skin rash should therefore not exclude the possibility of VZV CNS infection. 1,3,4 There were two fatalities despite early and adequate treatment with intravenous aciclovir and both patients were considered as immunosuppressed. One patient was on long term steroid therapy for connective tissue disorder and the other patient had uncontrolled diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of the typical skin rash should therefore not exclude the possibility of VZV CNS infection. 1,3,4 There were two fatalities despite early and adequate treatment with intravenous aciclovir and both patients were considered as immunosuppressed. One patient was on long term steroid therapy for connective tissue disorder and the other patient had uncontrolled diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha herpes viruses cause central nervous system (CNS) infections during primary infection or following reactivation from the latent state. [1][2][3][4][5] Patients with CNS infections develop a wide range of clinical features including headache, fever, seizures, altered behavior and altered level of consciousness though these may not be present in all patients. Clinical manifestations may be atypical, and diagnosis can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…VZV encephalitis is an uncommon complication of immunosuppressive treatment with mean annual incidence of 3 cases per 100,000 inhabitants [7]. Delayed diagnosis and treatment of VZV encephalitis in patients who presented with non-specific symptoms in the absence of skin lesions can have grave outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A large tertiary hospital-based series studied the epidemiological characteristics of central nervous system (CNS) infection by VZV in patients older than 65 years of age and reported mean annual incidence of VZV CNS infection of 0.003%. 7 On literature review, only a handful of cases have been reported of VZV reactivation in immunocompetent patients, most of which involved adult or elderly patients. [8][9][10][11][12] For proper diagnosis, CSF analysis using molecular biology tests such as PCR-to detect viral particles is considered a cornerstone.…”
Section: Journal Of Investigative Medicine High Impact Case Reportsmentioning
confidence: 99%